2010
DOI: 10.1073/pnas.1012468108
|View full text |Cite
|
Sign up to set email alerts
|

Formation of benzene in the interstellar medium

Abstract: Polycyclic aromatic hydrocarbons and related species have been suggested to play a key role in the astrochemical evolution of the interstellar medium, but the formation mechanism of even their simplest building block—the aromatic benzene molecule—has remained elusive for decades. Here we demonstrate in crossed molecular beam experiments combined with electronic structure and statistical calculations that benzene (C 6 H 6 ) can be synthesized via the barrierless, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
187
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 153 publications
(202 citation statements)
references
References 44 publications
13
187
2
Order By: Relevance
“…37,38 Another recent study implicates 1,3-butadiene in the formation of benzene in the interstellar medium via reaction with the C 2 H radical. 7 Furthermore, the modeling contained in that study concluded that neutral-neutral chemistry is the dominant source of benzene in the Taurus Molecular Cloud (TMC-1). The postulated chemical mechanism relies on CH + C 3 H 6 → 1,3-butadiene + H reaction which is then followed by 1,3-butadiene + C 2 H → c-C 6 H 6 + H. 7 Our results reported here provide the first direct evidence that 1,3-butadiene is the dominant product of the CH + propene reaction, in support of this assumption.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…37,38 Another recent study implicates 1,3-butadiene in the formation of benzene in the interstellar medium via reaction with the C 2 H radical. 7 Furthermore, the modeling contained in that study concluded that neutral-neutral chemistry is the dominant source of benzene in the Taurus Molecular Cloud (TMC-1). The postulated chemical mechanism relies on CH + C 3 H 6 → 1,3-butadiene + H reaction which is then followed by 1,3-butadiene + C 2 H → c-C 6 H 6 + H. 7 Our results reported here provide the first direct evidence that 1,3-butadiene is the dominant product of the CH + propene reaction, in support of this assumption.…”
Section: Resultsmentioning
confidence: 99%
“…7 Furthermore, the modeling contained in that study concluded that neutral-neutral chemistry is the dominant source of benzene in the Taurus Molecular Cloud (TMC-1). The postulated chemical mechanism relies on CH + C 3 H 6 → 1,3-butadiene + H reaction which is then followed by 1,3-butadiene + C 2 H → c-C 6 H 6 + H. 7 Our results reported here provide the first direct evidence that 1,3-butadiene is the dominant product of the CH + propene reaction, in support of this assumption. Interestingly, the significant branching fraction for production of 1,2-butadiene may warrant further investigation into its role in the chemistry of hydrocarbon-rich environments.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…C 6 H 6 is a precursor of interstellar polycyclic aromatic hydrocarbons (PAHs) and hydrogenated amorphous carbon grains (aromatic/aliphatic mixture) (44)(45)(46). Its structure is representative of the peripheral sites of a PAH.…”
Section: Discussionmentioning
confidence: 99%
“…One example of a ring formation reaction is the C 2 H + 1,3-butadiene reaction that has been shown, under single collision conditions to form benzene + H at 40% product yield. 4 For the analogous CN + 1,3-butadiene reaction, however, no ring-closure pathways to pyridine are significantly competitive -only traces of pyridine are reported -due to high reaction barriers compared to linear isobaric species. 15 As shown in the next section, CN does rapidly react with aromatic species and is implicated in high order ring-formation mechanisms.…”
Section: Methodsmentioning
confidence: 99%